Metagenomic analysis evidences a core virome in Anopheles darlingi from three contrasting Colombian ecoregions - Juan C. Hernandez-Valencia; Giovan F. Gómez; Margarita M. Correa (PLoS ONE, 2025)
Anopheles darlingi is a main malaria vector in the neotropical region, but its viral component is not well studied, especially in the neotropics. This work aimed to analyze the virome in Anopheles darlingi from malaria endemic regions of Colombia. Specimens were collected from the Bajo Cauca, Chocoan Pacific and northwestern Amazonas regions and analyzed using an RNA-Seq approach. Results revealed a variety of RNA viral sequences with homology to those of Insect-Specific Viruses belonging to Rhabdoviridae, Partitiviridae, Metaviridae, Tymoviridae, Phasmaviridae, Totiviridae, Ortervirales and Riboviria. Despite geographical and ecological differences among regions, the An. darlingi viral composition remains consistent in different areas, with a core group of viral operational taxonomic units-vOTUs shared by the populations. Furthermore, diversity analysis uncovered greater dissimilarities in viral sequence among mosquitoes from geographically distant regions, particularly evident between populations located at both sides of the Andes Mountain range. This study provides the first characterization of the metavirome in An. darlingi from Colombia and lays the foundation for future research on the complex interactions among viruses, hosts, and microbiota; it also opens a new line of investigation on the viruses in Anopheles populations of Colombia.